2010
DOI: 10.4028/www.scientific.net/msf.667-669.1183
|View full text |Cite
|
Sign up to set email alerts
|

The Aspects of Practical Application of Ultrafine-Grained Titanium Alloys Produced by Severe Plastic Deformation

Abstract: The mechanical and physical properties of ultrafine-grained titanium alloys produced by severe plastic deformation are considered. It is found that the formation of ultrafine-grained structure in these materials causes a significant enhancement in their mechanical properties at room temperature and in their resistance to hydrogen embrittlement as well as a change in their acoustic properties. Moreover, superplasticity is realized in these materials at less elevated temperatures relative to the respective coars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…1, b). This character of flow curves is often observed during superplastic deformation of submicro-and nanocryctalline metals and alloys [1][2].…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…1, b). This character of flow curves is often observed during superplastic deformation of submicro-and nanocryctalline metals and alloys [1][2].…”
Section: Resultsmentioning
confidence: 62%
“…Interest in such materials is primarily caused by their unique physical-mechanical properties that are substantially different from those of coarse-and fine-grained analogs. For example, for SMC (α + β) titanium alloys superplastic flow is observed already at 873-973 K [1][2], whereas for fine-grained (grain size 2-10 µm) alloys it is observed at temperatures above 1100 K [3].…”
Section: Introductionmentioning
confidence: 99%
“…However, the real application of UFG Ti alloys in aircraft engine building requires studying a whole range of mechanical properties, including long-term strength at operating temperatures [40,41]. The previously conducted long-term strength tests of the UFG Ti-6Al-4V alloy at operating temperatures (not higher than 350 • C) show its obvious advantage over its coarse-grained counterpart [27].…”
Section: Discussionmentioning
confidence: 99%
“…Such a behavior makes grain refinement an efficient factor for improving a material's resistance to hydrogen embrittlement, underlain by a decrease in hydrogen's 'effective' diffusion rate value, due to a decrease in the relative fraction of hydrogen per area unit of a grain boundary. Another paper [99] examined the effect of increasing the resistance to hydrogen embrittlement of the UFG Ti-6Al-4V alloy, by means of increasing its maximum permissible hydrogen concentration in comparison to the CG state. A paper [100] showed that the elongation and impact toughness of nanocrystalline Ti with a hydrogen content from 0.1 to 5 at.% are practically the same, while in microcrystalline Ti they decrease when hydrogen is added, which indicates a lower risk of hydride-induced embrittlement in nanocrystalline Ti than in its microcrystalline counterpart.…”
Section: On the Prospects Of The Practical Application Of Ti-based Ma...mentioning
confidence: 99%